Reavaliando a vulnerabilidade externa da economia brasileira - Fernando José da S. P. Ribeiro (Instituto de Pesquisa Econômica Aplicada (IPEA), 2016)
– This paper aims to reapproach the external vulnerability of the brazilian economy, based on the the theory and considering the new conditions of the world economy and the transformations that carachterized the Brazilian economy in this century, in the period or rapid growth (until 2010) as well as in the period of deceleration and crisis that followed. Departing from a digression about the historical behavior of the current account balance and from a brief revision of the theoretical and empirical literature concerning the theme, the paper evaluates de degree of external vulnerability of the country through the analysis of a group of variables usually referred in the literature as external vulnerability Two main conclusions are highlighted. First, the country faces, today, a reasonably comfortable situation in terms of external vulnerability, especially due to the accumulation of a huge volume of international reserves and to a more favorable profile of the external financing flows. This made the country less vulnerable to currency crises or to short term problems of external financing. The second conclusion is that there were no advances in overcoming the structural problems with the aim of mitigating the external vulnerability in a more perennial manner, which would mean developing conditions to control the cycles of expansion and contraction of the current account balance, providing a more balanced trajectory and one that were compatible with a reasonable and sustained rate of economic growth in the long term.
Keywords: F32; F34; 330; external vulnerability; current account; balance of payments; exports; external liabilities